Social Investment Policy - A New Political Economy of Social Service Production - Monika Burmester; Norbert Wohlfahrt (Social Work & Society, 2020)
The welfare state, for years, is under attack to improve its effectiveness and efficiency. In this environment, the interpretation of parts of social expenditure as investments leads to a shift in the goals of social expenditures. Social services should no longer be viewed as a reallocation tool to improve those who are in need, but as an investment in human capital. As investments generate returns, the question arises, what kind of return social investment generates and how to measure it. This question is discussed in the article. It also points to the consequences of social investment policy for professional social work. Social services, that are interpreted as investments, have to demonstrate, that they achieve returns. And these returns are related to predefined goal. Professional social work is only acting effectively if it produces a measurable benefit for society, called (social) impact.